Transcriptomic analysis identifies oxidative stress-related hub genes and key pathways in sperm maturation - Abroudi, Ali Shakeri; Azizi, Hossein; Qadir, Vyan A.; Djamali, Melika; Alsaffar, Marwa Fadhil; Skutella, Thomas (Antioxidants, 2025)
Background: Oxidative stress is a critical factor contributing to male infertility, impairing spermatogonial stem cells (SSCs) and disrupting normal s...